Determinants of Disposal of Disposable Diapers Among Caregivers in Kisumu City, Kenya - Samuel Eshitemi; Lakati, Alice; Karama, Mohammed (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
Background: A disposable diaper harbor feces and hazardous chemicals that if improperly handled and disposed, can lead to diseases and pollution. Objective: To assess determinants for disposal of disposable diapers in Kisumu city. Methods: A cross-section design was used. 246 Caregivers with children < 3 years were selected and ata was collected using a semi-structured questionnaire. Data was analysed in SPSS and both descriptive and inferential statistics were performed with significance level set at 0.05. Results: Majority (86.5%) of the caregivers were women. The mean age of caregivers was 29.3 years (±= 6.86). mean household size was 5, most (92.3%) households were male headed with an average monthly income of KES 21,833; Majority of mothers (73.1%) and fathers (93.2%) had attained secondary level of education. The usage of disposal diapers was 95.93% with appropriate disposal at 41.3%. Variables significantly (P<0.05) associated with appropriate disposal of diapers were: Sex of the household head; Mother with high school education; father with high school education; home ownership status; and availability of onsite sanitation. Conclusions: Maternal literacy and household income are key determinants for disposal of diapers. Knowledge on risks posed by diapers is high but it has not translated into proper disposal practice.